The Fulcrum of Structure-Agency: History and Sociology of Sugar Haciendas in Colonial Negros - Aguilar, Filomeno V, Jr (Archīum Ateneo, 2013)
In retracing the author's personal trajectory into interdisciplinarity, this article focuses on the reconsiderations of theories and concepts in historical materialism and related fields of knowledge that he grappled with as a graduate student in the early 1990s in the process of analyzing the historical structuring of sugar haciendas in colonial Negros Occidental. These theoretical reconsiderations inform the five propositions that are offered as an alternative to five erroneous historical assertions about Negros then extant in the literature. These theoretical reconsiderations also explain why and how the author's work on Negros is both history and sociology.